A Structure Shaped by Fire, but Also Water: Ecological Consequences of the Variability in Bark Properties Across 31 Species From the Brazilian Cerrado - Loram-Lourenço, Lucas; Farnese, Fernanda dos Santos; Sousa, Letícia Ferreira de; Alves, Rauander Douglas Ferreira Barros; Andrade, Maria Clara Pereira de; Almeida, Sabrina Emanuella da Silva; Moura, Luciana Minervina de Freitas; Costa, Alan Carlos; Silva, Fabiano Guimarães; Galmés, Jeroni; Cochard, Hervé; Franco, Augusto Cesar; et al. (Frontiers in Plant Science, 2020)
Bark is a structure involved in multiple physiological functions, but which has been traditionally associated with protection against fire. Thus, little is known about how the morpho-anatomical variations of this structure are related to different ecological pressures strategies, especially in tropical savanna species, which are commonly subjected to frequent fire and drought events. Here we evaluated how the structural and functional variations of bark are related to the processes of resilience and resistance to fire, as well as transport and storage of water in 31 native species from the Brazilian Cerrado. Because of their thick bark, none of the trees analysed were top-killed after a severe fire event. The structural and functional variations of the bark were also associated with water storage and transport, functions related to properties of the inner bark. In fact, species with a thicker and less dense inner bark were the ones that had the highest water contents in the wood, bark, and leaves. Lower bark density was also related to higher stem hydraulic conductivity, carbon assimilation, and growth. Overall, we provide strong evidence that in addition to protection from fire, the relative investment in bark might also reflect different strategies of water use and conservation among many Cerrado tree species.